2003
DOI: 10.4028/www.scientific.net/kem.240-242.813
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Ceramic Wear Couples in Total Hip Arthroplasty

Abstract: The wear rate of modern ceramic wear couples with hip simulators is extremely low (0.001mm/year, 0.5mg/year), but there are only few data concerning the in-vivo wear rate. We have performed a retrieval analysis of two ceramic couples. The ceramic heads and the cup inserts were retrieved after 24 months of in-vivo function. There were no scratches and no sign of third body wear. The articulating surfaces were still in a polished state. The wear rate was below detection limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…6 Extensive testing has shown that Al 2 O 3 implants that meet or exceed ISO standards have excellent resistance to dynamic and impact fatigue and also resist subcritical crack growth. 19,20 An increase in average grain size to >7 m can decrease mechanical properties by ∼20%. High concentrations of sintering aids must be avoided, because they remain in the grain boundaries and degrade fatigue resistance, especially in the corrosive physiological environment.…”
Section: (3) Almost-inert Crystalline Bioceramicsmentioning
confidence: 99%
“…6 Extensive testing has shown that Al 2 O 3 implants that meet or exceed ISO standards have excellent resistance to dynamic and impact fatigue and also resist subcritical crack growth. 19,20 An increase in average grain size to >7 m can decrease mechanical properties by ∼20%. High concentrations of sintering aids must be avoided, because they remain in the grain boundaries and degrade fatigue resistance, especially in the corrosive physiological environment.…”
Section: (3) Almost-inert Crystalline Bioceramicsmentioning
confidence: 99%
“…Alumina turns white when it is sintered in reducing atmosphere or if it contains traces of silica (Willmann, 2003). Alumina is generally white but can sometimes be pink (88% alumina) or brown (96% alumina).…”
Section: Physical Properties Of Aluminamentioning
confidence: 99%
“…A retrieval analysis of two ceramic couples was conducted by Willmann et al (2003). Two hemispheric press-fi t cups with a Biolox® Forte ceramic inlay were retrieved and analysed after 24 months of in vivo function.…”
Section: Bioloxmentioning
confidence: 99%
“…Many past/current methods—oil drop counting, shadow graphs, gravimetric measurements, radiostereometric analysis (RSA), and coordinate measuring machines (CMM)—yield ambiguous results. In addition, continuing improvements in implant materials (ceramic–ceramic, and metal–metal) produce ever‐smaller amounts of wear that must be accurately quantified to predict possible negative side effects 1–8…”
Section: Introductionmentioning
confidence: 99%
“…In addition, continuing improvements in implant materials (ceramicceramic, and metal-metal) produce ever-smaller amounts of wear that must be accurately quantified to predict possible negative side effects. [1][2][3][4][5][6][7][8] Even after decades of use, our ability to provide quantitative analysis of implant wear is limited. For example, the in vitro wear rate for alumina femoral heads articulating against alumina acetabular cups (alumina-on-alumina) cannot currently be quantified via gravimetric measurement making quantitative estimates of long-term behavior in vivo problematic.…”
Section: Introductionmentioning
confidence: 99%